Menyusuri Mitologi dan Ritual Sebagai Elemen Budaya Yang Menjadi Jejak Pembentuk Realitas Pandangan Dunia Orang Bolaang Mongondow - Marde Christian Stenly Mawikere; Sudiria Hura (Pascasarjana IAKN Manado, 2020)
This research is an investigation into traces of the myths and rituals of the Bolaang Mongondow people that shape the reality of their world view. The study was carried out using a descriptive method that was built from diverse and relevant scientific literature research. The results of this study show the components of the traditional culture of the Bolaang Mongondow people, namely the stories of the past and certain traditional ceremonies that shape their worldview concept, including their beliefs that have a background in folk religion with animism-dynamism and traditional social structures which is in the form of a monarchy. This then shapes their world view which continues to influence their attitudes and behaviors even though there have been social changes because time always points forward. Thus it can determine and recommend a complete service approach that is contextual and relevant to Bolaang Mongondow people, both spiritual, social, economic, educational, and so on.